2013
DOI: 10.1038/nn.3550
|View full text |Cite
|
Sign up to set email alerts
|

Network state-dependent inhibition of identified hippocampal CA3 axo-axonic cells in vivo

Abstract: Hippocampal sharp waves are population discharges initiated by an unknown mechanism in pyramidal cell networks of CA3. Axo-axonic cells (AACs) regulate action potential generation through GABAergic synapses on the axon initial segment. We found that CA3 AACs in anesthetized rats and AACs in freely moving rats stopped firing during sharp waves, when pyramidal cells fire most. AACs fired strongly and rhythmically around the peak of theta oscillations, when pyramidal cells fire at low probability. Distinguishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
208
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(226 citation statements)
references
References 51 publications
(105 reference statements)
14
208
4
Order By: Relevance
“…In support of this hypothesis, adding the muscarinergic drug carbachol to the perfusion solution in in vitro investigation also abolishes spontaneously occurring SPW-Rs (16). Alternatively, or in addition, suppression of hippocampal axo-axonic neurons by transiently bursting septal GABAergic neurons may initiate SPW-Rs (40). This suggestion, however, leaves open the question of why a specific subset of septal inhibitory cells bursts during reduced cholinergic activity in the absence of theta oscillation.…”
Section: Discussionmentioning
confidence: 89%
“…In support of this hypothesis, adding the muscarinergic drug carbachol to the perfusion solution in in vitro investigation also abolishes spontaneously occurring SPW-Rs (16). Alternatively, or in addition, suppression of hippocampal axo-axonic neurons by transiently bursting septal GABAergic neurons may initiate SPW-Rs (40). This suggestion, however, leaves open the question of why a specific subset of septal inhibitory cells bursts during reduced cholinergic activity in the absence of theta oscillation.…”
Section: Discussionmentioning
confidence: 89%
“…88 Moreover, axo-axonic cells in the CA3 network show significant phase coupling to hippocampal gamma oscillations in vivo, comparable in strength and phase to those of pyramidal cells and PV þ basket cells. 91 In the rat somatosensory cortex, axoaxonic cells have been reported to depolarize pyramidal cells and thus initiate stereotyped series of synaptic events in neuronal networks because of a depolarized reversal potential for axonal relative to perisomatic GABAergic inputs. 92 Further studies are required to clarify the crucial role of axo-axonic cells as suggested by their morphology and strategical positioning.…”
Section: Hippocampal Gamma Oscillations and Fast-spiking Inhibitory Imentioning
confidence: 99%
“…To examine whether sEPSC supra reinforcement is driven by reward stimulation or by contingency of electrical stimulation of the brain, we applied contingent electrical stimulation to the ventromedial thalamus, a reward-unrelated thalamic nucleus that is located close to the LH and projects to the hippocampus (Su and Bentivoglio, 1990;Varela et al, 2013). Stimulation to the ventromedial thalamus was not shown to increase the sEPSC supra frequency, at least during our 25 min observation period ( p ϭ 0.11, t 4 ϭ 2.04, paired t test, n ϭ 5 cells; Fig.…”
Section: Reinforcement Of Synaptic Activitymentioning
confidence: 99%
“…Cell assembly dynamics have been well documented in coordinated activity of the hippocampus (Harris et al, 2003;, a brain region involved in certain forms of learning and memory. For example, cell assemblies that appeared during learning are often spontaneously reactivated as synchronous barrages during quiet awake states or slow-wave sleep (Buzsáki et al, 1983;Wilson and McNaughton, 1994;Lee and Wilson, 2002). Therefore, barrage activities of hippocampal neurons serve as an experimental model with which to investigate neural processes underlying learning and memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation